Closure: a mind/brain perspective - Hart, Jeremy (College of Music, 2025)
The topic of closure - that sense of logical completion and conclusion - is often given much weight in the discussion of Western Classical music. However, this discussion enters uncertain territory when dealing with works which eschew the tonal-syntactic structure of the common practice period; a challenge common to music of the Twentieth Century. This dissertation concerns itself with the question of how closure can be achieved under these conditions. Most of the literature approaches this issue by analysing musical devices or procedures which composers employ at non-tonal musical endings, but this is usually done without first establishing criteria for distinguishing between endings that articulate closure and those that do not. To address this, I begin by proposing a definition of closure as a concept and then explore the cognitive underpinnings of this sensation through a review of Event Segmentation Theory. This allows me to construct a lens through which to revisit the existing work on non tonal endings and discuss their potential closural effect. My discussion concludes that, in the absence of a well-developed or commonly understood grammatical-semantic system, music requires a linear or directed process with a limiting element (either a process which is self limiting, one that proceeds toward a previously stated limit, or one that is interrupted by a significant modification) for it to stimulate a sense of closure. A notable exception to this was the possibility of closure as a result of high processing effort when locating an ending. I believe that these conclusions are valuable to the formal analysis or composition of non-tonal works within the Western Classical tradition